TEACHING ENGLISH ONLINE TO CHILDREN WHO ARE SOME DISABILITIES ON AUTISM SPECTRUM DISORDER (ASD) AND DOWN SYNDROME AMID(DSA) IN THE PERIOD OF PANDEMIC - Azizova Durdona Avazbek qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The unparalleled circumstances brought about by the covid-19 pandemic have compelled both students and educators to adjust to novel routines and technological tools to satisfy the educational demands arising from this global health crisis. This case study examined a methodological intervention involving students at an English school catering to individuals with special needs in Manizales (Colombia). Our team, consisting of two university lecturers and seven pre-service educators, conducted online English classes for 17 students diagnosed with autism spectrum disorder (ASD) and 13 with Down syndrome (DS). To achieve this, we applied the principles of universal design for learning (UDL) alongside an eclectic method that integrates strategies from three specific approaches: The Presentation, Practice, and Production (PPP) approach, the Treatment and Education of Autistic and Related Communication-Handicapped Children (TEACCH) model, and a behavioral management framework. The aim of this research was to assess the effect of implementing these strategies on the English language learning (ELL) process for ASD and DS students. We employed three data collection methods, which included two surveys directed at parents and a researcher’s journal. The results revealed that: (a) the integration of diverse stimuli and methodological strategies from multiple approaches facilitated learning, (b) the incorporation of images and pictograms enhanced memory retention, (c) establishing clear routines encouraged the development of self-regulation skills, and (d) the challenges faced by families and students were transformed into opportunities. It was concluded that teaching English online to students with ASD and DS necessitates a deep understanding of their conditions and the implementation of appropriate strategies derived from an eclectic instructional model.